What do books in the home proxy for? A cautionary tale - Engzell, P (SAGE Publications, 2019)
In studies of educational achievement, students’ self-reported number of books in the family home is a frequently used proxy for social, cultural, and economic background. Absent hard evidence about what this variable captures or how well, its use has been motivated by strong associations with student outcomes. I show that these associations rest on two types of endogeneity: Low achievers accrue fewer books and are also prone to underestimate their number. The conclusion is substantiated both by comparing reports by students and their parents and by the fact that girls report on average higher numbers despite being similar to boys on other measures of social background. The endogenous bias is large enough to overturn classical attenuation bias; it distorts cross-country patterns and invalidates many common study designs. These findings serve as a caution against overreliance on standard regression assumptions and contribute to ongoing debates about the empirical robustness of social science.